1995
DOI: 10.1128/mcb.15.11.6420
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Poly(A) Site Use during Mouse B-Cell Development Involves a Change in the Binding of a General Polyadenylation Factor in a B-Cell Stage-Specific Manner

Abstract: Immunoglobulin (Ig) heavy-chain proteins exist in two forms, differing only at their carboxyl termini. The membranebound antigen receptor is found on the surface of early or memory B cells, while the secreted form is produced by plasma cells. The mRNAs for the two protein forms are derived from a single pre-mRNA that is alternatively processed at the 3Ј end (1,8,44,45). The 3Ј end of the secretion-specific (sec) mRNA is encoded by the last constant-region exon; the sec poly(A) site is about 100 nucleotides dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
81
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 78 publications
(62 reference statements)
7
81
0
Order By: Relevance
“…In human, a shift in poly(A) site choice in the IgM heavy-chain gene occurs during B cell maturation. An increase in CstF-64 protein amount or activity during differentiation has been proposed to be involved in utilization of a weak proximal poly(A) site of the gene, which generates a transcript coding for a secreted protein in mature B cells (24,25). In Drosophila, we previously showed that the Su(f) protein is required for tissue-specific utilization of a regulated poly(A) site in intron 4 of the su(f) gene (19,20).…”
Section: Cstf and The Regulation Of Alternative Poly(a) Site Choice Imentioning
confidence: 99%
See 1 more Smart Citation
“…In human, a shift in poly(A) site choice in the IgM heavy-chain gene occurs during B cell maturation. An increase in CstF-64 protein amount or activity during differentiation has been proposed to be involved in utilization of a weak proximal poly(A) site of the gene, which generates a transcript coding for a secreted protein in mature B cells (24,25). In Drosophila, we previously showed that the Su(f) protein is required for tissue-specific utilization of a regulated poly(A) site in intron 4 of the su(f) gene (19,20).…”
Section: Cstf and The Regulation Of Alternative Poly(a) Site Choice Imentioning
confidence: 99%
“…In vitro, affinity of CstF for the U͞GU-rich elements, which are highly variable in sequence, defines the efficiency of poly(A) sites by determining the stability of the cleavage complex on the pre-mRNA (22). In mammalian cells, several studies have correlated shifts in the choice of poly(A) sites with quantitative or qualitative variations of CstF-64 (23)(24)(25)(26)(27). In Drosophila, we and others have shown that modulation of su(f) activity in su(f) mutants affects the utilization of alternative poly(A) sites in the f 1 mutation, the Adh͞Adhr locus, and the su(f) gene itself (19,20,28,29).…”
mentioning
confidence: 99%
“…The decision between the synthesis of membrane vs secreted Igs is made by choice of polyadenylation site (9), but exactly what regulates the levels of these different mRNAs is not known. Clearly, the inability to generate an mRNA that encodes the secreted -chain is not automatically linked to an increase in the synthesis of the membrane bound product, notwithstanding seemingly adequate secretory capacity (7).…”
mentioning
confidence: 99%
“…Protein concentration was measured by the Bradford assay. UV crosslinking reactions contained 5 to 10 μg of nuclear extract protein, 10 to 20 fmol of substrate RNA (50,000 to 100,000 cpm), 1 mM ATP, 0.7 mM MgCl 2 , and 40 ng of carrier tRNA in a 25 μl final volume of buffer (20 mM N-2-hydroxyethylpiperazine-N′-2-ethanesulfonic acid (HEPES) pH 7.9, 0.2 mM EDTA, 10% glycerol, and 150 mM KCl) [26]. Reaction mixtures were incubated for 5 to 10 min at 30°C and then subjected to UV crosslinking on ice for 10 min in a Stratalinker (1.8 x 10 6 μJ/cm 2 ).…”
Section: Uv Crosslinkingmentioning
confidence: 99%
“…Samples were treated with (1 mg/ml) at 37°C for 30 min. Proteins were boiled for 5 min in cracking buffer (80 mM Tris-Cl, pH 6.8, 0,1 M dithiothreitol, 2% sodium dodecyl sulfate (SDS), 10% glycerol, and 0.2% bromophenol blue) and separated in 10% SDS-polyacrylamide gels [26]. Binding of proteins to the RNA was visualized using storage phosphor imaging and quantified using ImageQuaNT software.…”
Section: Uv Crosslinkingmentioning
confidence: 99%